'Radical Interpretation' and the Assessment of Decision‐Making Capacity. (13th August 2013) - Banner, Natalie F.; Szmukler, George
Abstract: The assessment of patients' decision‐making capacity (DMC) has become an important area of clinical practice, and since it provides the gateway for a consideration of non‐consensual treatment, has major ethical implications. Tests of DMC such as under the Mental Capacity Act (2005) for England and Wales aim at supporting autonomy and reducing unwarranted paternalism by being 'procedural', focusing on how the person arrived at a treatment decision. In practice, it is difficult, especially in problematic or borderline cases, to avoid a consideration of beliefs and values; that is, of the substantive content of ideas rather than simple 'cognitive' or procedural abilities. However, little attention has been paid to how beliefs and values might be assessed in the clinical context and what kind of 'objectivity' is possible. We argue that key aspects of Donald Davidson's ideas of 'Radical Interpretation' and the 'Principle of Charity' provide useful guidance as to how clinicians might approach the question of whether an apparent disturbance in a person's thinking about beliefs or values undermines their DMC. A case example is provided, and a number of implications for clinical practice are discussed.